Mutation Update and Genotype–Phenotype Correlations of Novel and Previously Described Mutations in TPM2 and TPM3 Causing Congenital Myopathies. Issue 7 (1st May 2014) - Marttila, Minttu; Lehtokari, Vilma‐Lotta; Marston, Steven; Nyman, Tuula A.; Barnerias, Christine; Beggs, Alan H.; Bertini, Enrico; Ceyhan‐Birsoy, Özge; Cintas, Pascal; Gerard, Marion; Gilbert‐Dussardier, Brigitte; Hogue, Jacob S.; et al.
<x xml:space="preserve">Abstract</x> We present mutation update and genotype‐phenotype correlations for novel (16) and previously reported (31) mutations of the TPM2 and TPM3 genes causing nemaline myopathy, cap myopathy, core‐rod myopathy, congenital fibre‐type disproportion, distal arthrogryposes and Escobar syndrome. Included are 93 families: 53 with TPM2 mutations and 40 with TPM3 mutations. Six mutations cause increased Ca2+ sensitivity resulting in hypercontractile phenotypes. Our in silico predictions show that most mutations affect tropomyosin‐actin association or tropomyosin head‐to‐tail binding. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>